Overcoming bias a journalist's guide to culture & context - Christian, Sue Ellen 1966- (Routledge, 2021)
"In this practical and engaging new edition, experienced reporter and teacher Sue Ellen Christian offers a fully updated and fresh take on reporting without bias, examining the way that we categorize people, filter information and default to rehearsed ways of thinking. This book is about biases that affect journalism at every stage of reporting and writing. Included throughout are stories and advice from working reporters and editors, providing real-world voices and experiences, and covering questions of culture, stereotyping, sources, writing, editing, visuals and reflective practice. This advice and guidance is coupled with practical exercises that give readers the chance to apply what they learn. Christian provides a career-long foundation for those looking to edit their thinking and to champion a more inclusive and open-minded approach to multicultural society coverage. Offering a concise, readable and highly applicable guide to managing coverage of contemporary social issues, this book is an ideal resource for undergraduate and graduate students of journalism and early career journalists"--